Relationship between ABO Blood Groups and Rh Factor with COVID-19 in Nineveh Governorate - Mustafa, Rasha Jamal Al Deen (Iraqi Journal of Science, 2024)
ABO blood types and the Rh factor have recently been linked to an increased risk of developing the pandemic coronavirus disease 2019 (COVID-19) in individuals of different ethnic backgrounds. The conducted current study aimed to comprehend the relationship between this polymorphic apparatus and illness risk in Nineveh patients and healthy individuals. Recovery or death and two COVID-19 outcomes were also investigated. Many individuals including COVID-19 Nineveh patients had their ABO blood type and Rh factors determined. Thus, four groups (under therapy, rehabilitative, death, and healthy donors) were created from the research samples. The diagnosis kit RNA (PCR-Fluorescence Probing) was used to diagnose 2019 novel coronavirus (2019nCoV) for patients. The data was gathered from hospital records. The purpose of this study was to highlight significant data related to COVID-19 patients’ infection, symptoms and prognosis with respect to ABO blood type and Rh factor. Results of the current study included links between Rh factor and ABO blood types with increased infection potential, longer incubation times and fatal acute outcomes. Knowing that COVID-19 predisposing factors might help with patient survival, illness treatment and studying viral path physiology. A total of 2480 samples were ،distributed to control group and hospitalized patients with definite COVID-19 infection in isolation in the hospital in Mosul City for the period between 2nd December 2021 and 5th March 2022. The blood samples were obtained from patients and healthy donors by using kit for blood type identification, while the blood types of the deceased were taken from the hospital records. Several statistical tests were also conducted to find out the differences between the aforementioned groups. ANOVA was performed to investigate the correlation of ABO blood types with incidence of COVID-19 patients. The variables adopted in the analysis were age and sex. The study found that the difference between the association of each blood group with that of cases was significantly correlated (p = 0.00001). Out of total 975 patients 30.2% had blood group A, 27.3% had group B, 26.8% had group O and 15.7% had blood group AB. The study found that the number of recovered patients in 18-30 years age group was not significant among male and female population, while number of patients in other age groups in both male and female patients who finally recovered, was significantly lesser among patients with blood groups A and AB. There was a significant number of patients with blood group B in all the age groups except 31-35 years old. The study concluded that blood group B patients were severely affected by COVID-19.